Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence